Philosophy 167: Class 8 - Part 1 - Three Post-Copernican Generations- the Key Figures, and the Empirical Limitations of the Theorizing. - Smith, George E. (George Edwin), 1938- (Tufts Archival Research Center, 2015)
Synopsis: Introduces several key figures, including, Ren Descartes, Marin Mersenne, and Pierre Gassendi; notes that there are limits to theorizing.; Opening line: "So tonight we start what I like to call the third post-Copernican generation when turning to Descartes."; Duration: 10:26 minutes.; Segment: Class 8, Part 1.